Utilising single‐cell sequencing in clinical nutraceutical research: Recent progress and perspectives - Xiaoqiang Wang; Yin S. Chan; David Sadava; Shiuan Chen (Clinical and Translational Discovery)
Abstract Background Single‐cell sequencing technologies have revolutionised pharmaceutical research by providing in‐depth insights into human biology at the single‐cell level. These tools enable researchers to identify rare cell types and analyse cellular diversity within tissues, facilitating the discovery of new therapeutic targets and biomarkers. However, their application in nutraceutical research is still in its early stages. Main Body Unlike pharmaceuticals, which have well‐defined chemical structures and mechanisms, nutraceuticals are food‐based materials intended for specific medical purposes and often contain complex and diverse food chemicals. These molecules can work synergistically, producing multi‐targeted effects in various tissues. Traditional bulk profiling methods for tissues and tumours do not adequately capture cellular heterogeneity or specific cellular responses to treatments. Therefore, advanced single‐cell sequencing is crucial for dissecting tissues into distinct cell types, helping to clarify the underlying mechanisms at the cellular level. Many derivatives of functional foods have been marketed or assessed, demonstrating health benefits. However, mechanistic insights are lacking, with most current data derived from observational studies or traditional in vitro and in vivo models. Human clinical trials are needed to validate these nutraceutical effects and determine effective and safe dosages. Edible mushrooms have gained attention as nutraceuticals due to their medicinal properties. They have been observed to enhance immunity, reduce inflammation, and combat cancer. These effects have been attributed to their unique bioactive components and historical uses in traditional medicine. Epidemiological studies show that higher consumption of edible mushrooms is linked to a reduced risk of certain cancers. Conclusion In this review, we share important lessons learned in the design and execution of clinical trials focusing on white button mushrooms as anti‐cancer nutraceuticals. We demonstrate the use of single‐cell RNA sequencing (scRNA‐seq) in nutraceutical research to capture the nuanced biological responses and health effects of dietary foods and their constituents.